2020
DOI: 10.1007/s00264-020-04541-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radial extracorporeal shock wave therapy on clinical variables and isokinetic performance in patients with knee osteoarthritis: a prospective, randomized, single-blind and controlled trial

Abstract: Objective This study aims to compare the efficacy of r-ESWT treatment with sham-ESWT on pain, walking speed, physical function, and isokinetic muscle strength in knee osteoarthritis. Methods The study included 104 patients (mean age 61.0 ± 6.2 years; range 50 to 70 years) who were admitted to our outpatient clinic with newly diagnosed with knee osteoarthritis. Patients were randomly assigned to two groups. Both groups received transcutaneous electrical nerve stimulation for 30 minutes, hot pack for 40 minutes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
(19 reference statements)
0
27
1
Order By: Relevance
“…Uysal et al compared the efficacy of r-ESWT treatment with sham-ESWT for knee OA. They found r-ESWT to be more effective than sham-ESWT at improving pain, walking speed, physical function, and isokinetic muscle strength [ 23 ]. Investigating the effectiveness of f-ESWT in patients with knee OA, Lee et al found that f-ESWT in combination with physical therapy was superior to physical therapy alone in reducing pain and improving the functional status of knee OA patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uysal et al compared the efficacy of r-ESWT treatment with sham-ESWT for knee OA. They found r-ESWT to be more effective than sham-ESWT at improving pain, walking speed, physical function, and isokinetic muscle strength [ 23 ]. Investigating the effectiveness of f-ESWT in patients with knee OA, Lee et al found that f-ESWT in combination with physical therapy was superior to physical therapy alone in reducing pain and improving the functional status of knee OA patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may lead to different therapeutic effects between f-ESWT and r-ESWT [ 21 , 22 ]. Although shockwave therapy is not currently approved by the International Society for Medical Shockwave Treatment (ISMST) for treating OA, recent studies suggested that f-ESWT or r-ESWT could be effective at reducing pain and improving the functional status of knee OA patients [ 21 , 22 , 23 , 24 ]. To our knowledge, no prior studies have directly compared the effects of f-ESWT and r-ESWT in knee OA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, patients do not need to spend much time or money on ESWT. Because of these beneficial characteristics, ESWT has been a therapeutic option for the treatment of many musculoskeletal diseases ( 6 , 7 ), including plantar fasciitis ( 8 10 ), calcific shoulder tendinopathy ( 11 ), tennis elbow ( 12 ), trigger finger ( 13 ), knee osteoarthritis ( 14 ), and bone non-union ( 15 17 ). ESWT has also been utilized to treat wounds ( 18 – 21 ), urological diseases ( 22 24 ), and male erectile rejuvenation ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Zhong compared the treatment of ESWT with placebo on knee OA, and the VAS, WOMAC, Lequesne index are superior in the ESWT group [ 32 ]. Dr. Uysal also reported the radial ESWT has statistically significant superior improvement than sham ESWT in all parameters, including VAS score, knee ROM, 20-m walk test, and Lequesne’s disability scores [ 33 ]. In our study, the ESWT group improved VAS, KOOS, WOMAC, and IKDC score statistically significantly one month after treatment, and the effect lasted for one year.…”
Section: Discussionmentioning
confidence: 99%